Socio-economic impacts of brucellosis on livestock production and reproduction performance in Koibatek and Marigat regions, Baringo County, Kenya - Lokamar, Peter N. (BMC Vet Res, 2020)
BACKGROUND: Brucellosis in Africa is caused by Brucella species transmitted through contaminated or contacts with infected animals or their carcasses. The disease reduces livestock production and reproduction performance evident by frequent episodes of abortion, still births, swollen testes, weak calves/lambs and swollen joints. However, the socio-economic impacts of these brucellosis-associated symptoms on milk, fat, meat and blood production, infertility, sale value, dowry and costs of treatment has not been evaluated extensively in developing countries. In Baringo County, Kenya, there is a continuous movement of cattle as a result of trade and grazing, which predisposes many herds to brucellosis infection. The objective of this study was to investigate the socio-economic impacts of Brucella infection on production systems for sheep, goats, cattle and camels and explore the impact of brucellosis on livestock production and reproduction performance among livestock keeping communities in Baringo County, Kenya. The study adopted a cross-sectional survey using quantitative data collection methods. RESULTS: Results demonstrated an impact on milk production in suspected brucellosis cases resulting from abortions (OR = 0.151, P < 0.0001) and swollen joints (OR = 2.881, P < 0.0001). In terms of infertility, abortion as a symptom of brucellosis (OR = 0.440, P = 0.002), still birth (OR = 0.628, P = 0.042), and weak calf or lamb (OR = 0.525, P = 0.005) had an impact on infertility. In terms of sale value, abortion (OR = 0.385, P = 0.008), weak calf/lamb (OR = 2.963, P = 0.013) had an impact on sale value. Other analyses demonstrated that for dowry, swollen testes (OR = 5.351, P = 0.032), weak calf and lambs (OR = 0.364, P = 0.019) had a likelihood of reduction of dowry value. Finally, in terms of cost of treatment, abortion (OR = 0.449, P = 0.001), still births (OR = 0.208, P = 0.015), swollen testes (OR = 0.78, P = 0.014), weak calf/lambs (OR = 0.178, P = 0.007) and swollen joints (OR = 0.217, P = 0.003) significantly increased the costs of treatments. There was no impact on fat and meat and blood production. CONCLUSION: Even though there was a huge socio-economic impact on milk production, infertility, sale value, and dowry, it was the costs of treatment that was significantly impacted on all symptoms associated with brucellosis on this community. A ‘One Health’ approach in tackling the brucellosis menace as a holistic approach is recommended for both humans and their livestock.